(untitled) (World Economics and Finance Bulletin, 2024)
This research was conducted to see how digital transformation is in the banking industry, in terms of the challenges and opportunities of this digital transformation. Based on the literature research from several previous studies, it can be concluded that almost on average the results of previous research conducted by several studies state that digital transformation has a significant influence on banking development. Apart from that, with digital transformation providing new opportunities for banking, banking development has also increased due to this digital transformation.